HYPERTEXT BASED INTERACTIVE MEDIA ANALYSIS IN GROWING STUDENT READING INTEREST THROUGH ONLINE LEARNING - Aqidatul Izza; Munawir Munawir (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2021)
This study discusses the analysis of hypertext-based interactive media in fostering student interest in reading through online learning. The purpose of this study was to determine the use and effectiveness of hypertext-based interactive media use in fostering student reading interest through online learning and the impact of hypertext-based interactive media on students' reading interest through online learning conducted at MTsN 1 Sidoarjo. This study uses a descriptive research method with a qualitative approach. Data collection using, observation, questionnaires, interviews and documentation. The results showed that: 1) The results of the observations proved that students had good enthusiasm. In this learning, Islamic education teachers use interactive media in the form of power points; 2) PAI teachers make various efforts to foster students' reading interest when learning online, one of which is trying to get used to the small things that are applied to students by utilizing the media; 3) From the results of a questionnaire which shows that students' reading interest has increased even though gradually. This can be seen from the aspects of preference, interest, attention and involvement. Keywords: Interactive Media, Hypertext, Reading Interest